Quantifying the Sources of Firm Heterogeneity * - Hottman, Colin J.; Redding, Stephen J.; Weinstein, David E. (Quarterly Journal of Economics, 2016)
Abstract We develop and structurally estimate a model of heterogeneous multiproduct firms that can be used to decompose the firm-size distribution into the contributions of costs, “appeal” (quality or taste), markups, and product scope. Using Nielsen barcode data on prices and sales, we find that variation in firm appeal and product scope explains at least four fifths of the variation in firm sales. We show that the imperfect substitutability of products within firms, and the fact that larger firms supply more products than smaller firms, implies that standard productivity measures are highly dependent on implicit demand system assumptions and probably dramatically understate the relative productivity of the largest firms. Although most firms are well approximated by the monopolistic competition benchmark of constant markups, we find that the largest firms that account for most of aggregate sales depart substantially from this benchmark, and exhibit both variable markups and substantial cannibalization effects.